2007
DOI: 10.2527/jas.2006-651
|View full text |Cite
|
Sign up to set email alerts
|

Effect of field peas, chickpeas, and lentils on rumen fermentation, digestion, microbial protein synthesis, and feedlot performance in receiving diets for beef cattle

Abstract: Two experiments were conducted to evaluate the use of pulse grains in receiving diets for cattle. In Exp. 1, 8 Holstein (615 +/- 97 kg of initial BW) and 8 Angus-crossbred steers (403 +/- 73 kg of initial BW) fitted with ruminal and duodenal cannulas were blocked by breed and used in a randomized complete block design to assess the effects of pulse grain inclusion in receiving diets on intake, ruminal fermentation, and site of digestion. Experiment 2 was a 39-d feedlot receiving trial in which 176 mixed-breed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 32 publications
(40 reference statements)
1
13
2
Order By: Relevance
“…Reed et al (2004), however, reported that inclusion of field peas linearly decrease acetate molar proportion and do not have an effect on propionate and butyrate molar proportions. Contrary to the results presented in the present study, Gilbery et al (2007) found that inclusion of legume grains decrease acetate concentration. Volatile fatty acid concentration is regulated by the balance between production and absorption.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Reed et al (2004), however, reported that inclusion of field peas linearly decrease acetate molar proportion and do not have an effect on propionate and butyrate molar proportions. Contrary to the results presented in the present study, Gilbery et al (2007) found that inclusion of legume grains decrease acetate concentration. Volatile fatty acid concentration is regulated by the balance between production and absorption.…”
Section: Resultscontrasting
confidence: 99%
“…Castillo et al (2011) demonstrated that mature ewes can tolerate higher levels of CPB than primiparous (averaging 11 months old), which developed diarrhea when 0.50 kg kg -1 of CPB was included in their supplement, while multiparous ewes (averaging 36 months old) did not develop this metabolic disorder. Other studies have reported similar results when different legume grains were fed to ruminants (Surra et al, 1992;Singh et al, 2006;Gilbery et al, 2007). Patterson et al (1999) found that the inclusion of cull beans in the diets of steers decreased NDF degradability; these results are in contrast with those reported in this study.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…As a consequence, scientific research was directed to increase knowledge on cultivation, plant breeding and utilization as animal feed of these grain legumes [13][14][15][16][17][18][19][20][21][22][23]. Results showed that in ruminant, monogastric and avian animals at least a partial replacement of soybeans is feasible in intensive animal farming systems, whereas in low input or organic farming systems soybean can be completely replaced by grain legumes that can be grown on farm where soybean cultivation is not feasible [24].…”
Section: Strategies For Partial or Total Soybean Replacementmentioning
confidence: 99%